Pengaruh Aromaterapi Inhalasi Lemon terhadap Mual dan Muntah pada Ibu Hamil Trimester I - Eva Solena; Elvi Era Liesmayani; Ade Sudiar (Jurnal Bidan Mandiri, 2024)
Aromatherapy is therapy essential oil components from plants. According to studies around 40% of women have used lemon aromatherapy to relieve nausea and vomiting. Of these, 26.5% reported that the smell of lemon was an effective way to control the symptoms of nausea and vomiting. This study aims to determine the effect of lemon inhalation aromatherapy on nausea and vomiting in first trimester pregnant. This type of research is a Quasi Experiment with a One Group Pre-test Post-test research design. The population in this study were all pregnant women who experienced nausea and vomiting in the first trimester, totaling 28 people and a sample of 15 people. Sampling with purposive sampling technique. Bivariate analysis with t-dependent test. The results of the univariate study showed that the average frequency of nausea and vomiting in first trimester pregnant women before being given inhalation aromatherapy was 4.60 times, the median was 5 times with a standard deviation of 1.298 times. The lowest frequency of nausea and vomiting was 3 times and the highest was 7 times. The average frequency of nausea and vomiting in pregnant women in the first trimester after being given lemon inhalation aromatherapy was 3.87 times, the median was 4 times with a standard deviation of 1.302 times. The lowest frequency of nausea and vomiting was 2 times and the highest was 6 times. Statistical test results obtained p value (0.000) it can be concluded that there is an effect of lemon inhalation aromatherapy on nausea and vomiting in first trimester pregnant women. It is hoped that midwives can provide an alternative to lemon inhalation aromatherapy in reducing nausea and vomiting during pregnancy.